A phase 2 randomised discontinuation trial of cabozantinib in patients with ovarian carcinoma. (September 2017) - Vergote, Ignace B.; Smith, David C.; Berger, Raanan; Kurzrock, Razelle; Vogelzang, Nicholas J.; Sella, Avishay; Wheler, Jennifer; Lee, Yihua; Foster, Paul G.; Weitzman, Ron; Buckanovich, Ronald J.
Abstract: Background: Cabozantinib (XL184), an orally bioavailable inhibitor of vascular endothelial growth factor receptor 2 and MET, was assessed in a cohort of ovarian carcinoma patients as part of a phase 2 randomised discontinuation trial (RDT) with cohorts from nine different tumour types. Patients and methods: Patients received 100-mg cabozantinib daily. Those with stable disease (SD) per Response Evaluation Criteria in Solid Tumors at week 12 were randomised to cabozantinib or placebo. Primary end-points were objective response rate (ORR) at week 12 and progression-free survival (PFS) after random assignment. Results: Seventy patients with ovarian carcinoma, 50% of whom were platinum refractory/resistant, were enrolled in this RDT. Median PFS from day 1 was 5.5 months for all patients. The ORR at week 12 was 21%; one patient achieved a complete response (CR), and 14 patients (20%) achieved a confirmed partial response (PR). The overall disease control rate (CR + PR + SD) at week 12 was 50%. Throughout the study, 70% of the patients with ≥1 postbaseline scan had tumour regression, and randomisation was discontinued early. For patients with SD randomised to cabozantinib, PFS was 5.9 months after randomisation. The most common grade 3/4 adverse events were diarrhoea (14%), palmar-plantar erythrodysesthesia syndrome (6%), asthenia (6%), hypertension (6%) and neutropenia (6%). Dose reductions were required in 37% of the patients during the first 12 weeks. Conclusion: Cabozantinib demonstrates clinical activity, with acceptable toxicities, in patients with ovarian carcinoma based on ORR and regression of tumour target lesions. Registration: This trial is registered at ClinicalTrial.gov (NCT00940225 ). Highlights: Cabozantinib was evaluated in a phase 2 randomised discontinuation trial. Cabozantinib showed clinical activity in previously treated patients with ovarian cancer. The objective response rate at week 12 was 21%. At week 12, patients with stable disease were randomised to cabozantinib or placebo. Progression-free survival for cabozantinib after randomisation was 5.9 months.